The Role of Government Policy Toward Technology Continuance Intention on Digital Industry in Indonesia - Mohammad Fahmi Arkanuddin; Susanti; Mani Festati Broto (Universitas Djuanda, 2023)
The purpose of this study was to analyze the relationship of government policy to the variables of perceived convenience, perceived usefulness, and confirmation and to analyze the effect of government policy on technology continuance intention. The research approach uses quantitative and research instruments by distributing 120 questionnaires to users of digital applications (e-commerce and fintech). Data processing using the SEM-Amos analysis tool. The results indicate that government policy exhibits strong correlations with a perceived ease of use estimate of 0.648, a perceived usefulness estimate of 0.261, and a confirmation estimate of 0.640. Moreover, the study reveals that government policy significantly influences technology continuance intention estimate: 0.349, (p-value estimate: 0.027 < cut-off p-value of 0.050, critical ratio value: 2.204 > cut-off critical ratio value of 1.690). These findings underscore the crucial role of government policy in fostering the growth of the digital industry in Indonesia. The study demonstrates that government involvement in the digital industry is of utmost importance and significantly impacts technology continuance intention in the future.